Design and Performance of a Compact Air-Breathing Jet Hybrid-Electric Engine Coupled With Solid Oxide Fuel Cells - Ji, Zhixing; Qin, Jiang; Cheng, Kunlin; Liu, He; Zhang, Silong; Dong, Peng (Frontiers in Energy Research, 2021)
A compact air-breathing jet hybrid-electric engine coupled with solid oxide fuel cells (SOFC) is proposed to develop the propulsion system with high power-weight ratios and specific thrust. The heat exchanger for preheating air is integrated with nozzles. Therefore, the exhaust in the nozzle expands during the heat exchange with compressed air. The nozzle inlet temperature is obviously improved. SOFCs can directly utilize the fuel of liquid natural gas after being heated. The performance parameters of the engine are acquired according to the built thermodynamic and mass models. The main conclusions are as follows. 1) The specific thrust of the engine is improved by 20.25% compared with that of the traditional jet engine. As pressure ratios rise, the specific thrust increases up to 1.7 kN/(kg·s−1). Meanwhile, the nozzle inlet temperature decreases. However, the temperature increases for the traditional combustion engine. 2) The power-weight ratio of the engine is superior to that of internal combustion engines and inferior to that of turbine engines when the power density of SOFC would be assumed to be that predicted for 2030. 3) The total pressure recovery coefficients of SOFCs, combustors, and preheaters have an obvious influence on the specific thrust of the engine, and the power-weight ratio of the engine is strongly affected by the power density of SOFCs.